MODEL PEMBELAJARAN KETELADANAN BERBASIS AL-QUR’AN - Fatimah, Siti (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2024)
The writing of this paper aims to discuss the Qur'an-based Model of Islamic Learning. Learning is a process towards achieving the goals of education. In this case, the learning process determines where the learners will be taken. Various learning models are implemented to achieve the expected goals. One of the qur'an-based learning models is the Tadzkirah learning model. This research is a literature research using the method of tafsir ilmi, namely by collecting readings from books, articles, journals and dissertations that discuss education and learning and verses of the Qur'an on education and learning in the perspective of the Qur'an. From literature research can be concluded that in the Qur'an there are verses about the model of learning in the Qur'an based on the Qur'an. One of them is tadzkirah learning model. Tadzkirah's learning model departs from the conception of children learning better through activities to experience themselves in a natural environment